2020
DOI: 10.1101/2020.05.27.120113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The crystal structure of SnTox3 from the necrotrophic fungusParastagonospora nodorumreveals a unique effector fold and insights into Kex2 protease processing of fungal effectors

Abstract: SummaryPlant pathogens cause disease through secreted effector proteins, which act to modulate host physiology and promote infection. Typically, the sequences of effectors provide little functional information and further targeted experimentation is required. Here, we utilised a structure/function approach to study SnTox3, an effector from the necrotrophic fungal pathogen Parastagonospora nodorum, which causes cell death in wheat-lines carrying the sensitivity gene Snn3.We developed a workflow for the producti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 82 publications
1
17
0
Order By: Relevance
“…SnTox3 was cloned, expressed and purified as described previously (Zhang et al ., 2017; Outram et al ., 2020). SnTox3 P173S was cloned from synthetic DNA (IDT gBlock), expressed and purified as described for SnTox3 (Outram et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SnTox3 was cloned, expressed and purified as described previously (Zhang et al ., 2017; Outram et al ., 2020). SnTox3 P173S was cloned from synthetic DNA (IDT gBlock), expressed and purified as described for SnTox3 (Outram et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…SnTox3 was cloned, expressed and purified as described previously (Zhang et al ., 2017; Outram et al ., 2020). SnTox3 P173S was cloned from synthetic DNA (IDT gBlock), expressed and purified as described for SnTox3 (Outram et al ., 2020). Five TaPR1 genes (TaPR1‐1, ‐5, ‐7, ‐16 and ‐18, codon‐optimized for S. cerevisiae ), lacking their N‐terminal signal peptides as determined by SignalP (Almagro Armenteros et al ., 2019), and TaPR1‐7ΔCAPE1 (TaPR1‐7 without the last 11 amino acids) were cloned into the expression vector pMCSG7 using ligation‐independent cloning (LIC) (Eschenfeldt et al ., 2009; Supporting Information Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BLASTp search with the SnTox5 amino acid sequence showed that SnTox3 was the only hit in the NCBI non-redundant database and only showed 45% homology. Although this is not a high level of homology, it is interesting that SnTox3 is also a pre-pro protein with a Kex2 cleavage site (Liu et al 2009; Outram et al 2020) and structural homology is also observed based on similar placement of the cysteine residues, indicating a potentially similar mature protein structure. The Kex2 protease is unique to fungi and Outram et al (2020) showed that Kex2-processed pro-domain (K2PP) effectors were common in pathogenic fungi and included the P. nodorum effectors SnTox3 and SnToxA and now SnTox5.…”
Section: Discussionmentioning
confidence: 98%
“…The Kex2 protease is unique to fungi and Outram et al (2020) showed that Kex2-processed pro-domain (K2PP) effectors were common in pathogenic fungi and included the P. nodorum effectors SnTox3 and SnToxA and now SnTox5. Outram et al (2020) also presented the crystal structure of SnTox3 and experimentally demonstrated that the Kex2-processed pro-domain was critical for SnTox3 folding and activity. The validation of SnTox5 provides another K2PP effector interaction for further study of this class of effectors.…”
Section: Discussionmentioning
confidence: 99%